Local public policies address gender violence in Cuba: between dares and social reality of women victims (Encuentros, 2016)
Gender violence is a social problem in Cuba. However, there is no effective public policy for women victims. On all country, the attention to the phenomenon is so distances of womens´s reality. On this basis, we conducted a qualitative study in Moa, with the objective of analyzing the role of local governments in addressing the problem, since policies planned at national level do not give effective responses to that. 47 women victims with life histories were studied and interviewed in depth 2 men abusers and 25 key informants. The results showed that the cultural and geographic diversity of Cuba implies the need to manage local public policy for attention to gender violence and that these take into account such joints for treatment. Keywords: local public policies, gender violence, local human development, patriarchal culture, geographical space, culturalspace joints